(untitled) (Journal of Hama University, 2024)
Introduction and aim of the research: Referring to previous clinical studies, many techniques have been used to accelerate orthodontic treatment in adults. These studies have proposed many specific interventions to accelerate orthodontic treatment, such as applying chemicals topically and systemically, using low-energy lasers, surgical techniques, and electrical pulse therapy, but all of them require more studies to confirm its effectiveness, and they may lead to gingival recession and loss of alveolar bone, which means the use of these methods is limited. Injectable platelet-rich fibrin (I-PRF) is considered one of the modern methods used to accelerate orthodontic dental movement. This research aims to: evaluate the effect of treatment with injectable platelet-rich fibrin (I-PRF) on accelerating the alignment and leveling of crowded upper anterior teeth and reducing the time required to achieve this. Materials and Methods: fourteen patients who required all 1st premolars extraction for the correction of their class I and class II malocclusions with severe crowding incisors were included. The I-PRF were injected in the experimental group (n = 7) after 1st premolar extraction. Control group was received Placebo injection. Incisors leveling was assessed from the maxillary study models prepared just before orthodontic application (T0) and then at 1 month (T1), 2 months (T2), at the end of incisors leveling (T3). Primary Outcome Measure, is the time required to complete leveling and alignment stage. The Independent Sample T Test was used to study the significance of differences in the mean values of the time period required to complete treatment, While Secondary Outcome Measure, was the percentage of improvement in leveling and alignment phase in each period by using T-test for independent samples. Results: I-PRF groups showed a significant reduction in the amount of LII at T1 and T2 compared to the control group.